2002
DOI: 10.1590/s0074-02762002000900035
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis mansoni in Bananal (State of São Paulo, Brazil): I. Efficiency of diagnostic and treatment procedures

Abstract: Bananal is an important focus of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The stream runs for a length of 42 m, with an average width of 1.5 m and a depth of up to 1.5 m, before debouching into another stream with a larger volume. Previous studies indicated that B. tenagophila is the only Biomphalaria species present in this stream and in all water samples collected in the municipality of Bananal [28], [29].…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…The stream runs for a length of 42 m, with an average width of 1.5 m and a depth of up to 1.5 m, before debouching into another stream with a larger volume. Previous studies indicated that B. tenagophila is the only Biomphalaria species present in this stream and in all water samples collected in the municipality of Bananal [28], [29].…”
Section: Methodsmentioning
confidence: 66%
“…This municipality was chosen because the area had been studied previously and because well-documented data regarding schistosomiasis transmission in this area were available. These data clearly indicated that B. tenagophila is the only species of mollusk responsible for the transmission of the disease in this area [28], [29]. Adopted control measures, such as the treatment of people infected with S. mansoni, the use of molluscicides and the performance of basic sanitation services by technicians at residences in the urban area of the municipality, have reduced the schistosomiasis prevalence to below 1%.…”
Section: Discussionmentioning
confidence: 85%
“…4,13 In Brazil, several techniques have been tested in LEAs, such as São Paulo. 12,15,36,37 In Barra Mansa, as a result of implementation of a special program for controlling schistosomiasis (Programa Especial de Controle da Esquistossomose) in 1976, schistosomiasis prevalence was around 1%. 20 The aim of this study was to compare and evaluate the accuracy of the COPT, IFA-IgM, and parasitological diagnostic techniques in the identification of S. mansoni infections, by means of epidemiological inquiry of randomized fecal and serum samples from individuals living in areas peripheral to Barra Mansa, Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 99%
“…11 Also of concern is continued transmission by asymptomatic carriers who transmit the parasite in areas without adequate basic sanitation. 12 Thus, LEAs require close surveillance to prevent increased endemicity. 4 Within this context, immunodiagnostic techniques have been introduced into the schistosomiasis control programs of some countries, such as Venezuela 13 and China.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in children, who may experience delayed growth and develop anemia and chronic malnutrition [ 2 ]. Moreover, asymptomatic carriers can potentially transmit schistosomiasis in areas that lack adequate sanitation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%